The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/1517-869220192502197823
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Conditioning Training: Acute Effects on Mood State

Abstract: Introduction: The search for strategies aimed at reducing daily stress is increasing in the current literature. As a result, several types of fitness training are constantly being investigated for their influence on mood states. However, we know little about strategies that use higher intensities. Objective: To investigate the acute effects of an extreme conditioning training (ECT) session on the mood states of individuals with or without prior experience in this type of training. Methods: Volunteers were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…To assess the methodological quality of the studies, the recommendations of STROBE (Strengthening the [33] were used to evaluate the qualitative studies. This scale has 21 items, and each study was given a score from 0 to 21 and was coded as being of low (score of 0-7), medium (score of [8][9][10][11][12][13][14], or high quality (score of [14][15][16][17][18][19][20][21].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…To assess the methodological quality of the studies, the recommendations of STROBE (Strengthening the [33] were used to evaluate the qualitative studies. This scale has 21 items, and each study was given a score from 0 to 21 and was coded as being of low (score of 0-7), medium (score of [8][9][10][11][12][13][14], or high quality (score of [14][15][16][17][18][19][20][21].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Experimental studies have found no changes in mental health [44] and well-being after CrossFit training. Concerning the consequences of CrossFit training, in an acute effect, some studies have found that reaction time was impaired, and that there are mood changes after a CrossFit session [18,35]. Regarding chronic effects, a study showed that mood may be impaired [45].…”
Section: Experimental Studiesmentioning
confidence: 99%
See 3 more Smart Citations